Mendesain Ulang Peninjauan Kurikulum: Menyediakan Pendekatan Integratif Keberhasilan Siswa dengan Menggabungkan Konten Inti Akademik dan Keterampilan Masa Depan yang Diperlukan - Nawawi, Syu'aib (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Today unlike before, meeting the challenges of society demands educational excellence. However, there is a broad consensus that our education system fails to adequately prepare all students with important 21st century knowledge and skills needed to succeed in life, career and citizenship. Furthermore, 21st century skills can function as student learning outcomes, curriculum can be built around its development, teacher professional development emphasizes learning, and various learning environments are developed by promoting it. Wherever we turn, we are faced with a storm or turulence called VUCA - volatility, uncertainty, complexity, and ambiguity. the education sector has not been immune to this turbulence. This paper aims to describe the steps in designing a curriculum: by providing an integrative approach to student success by combining core academic content and future skills needed. The results of the discussion concluded: 1) Core State Standards and Partnerships for Skills of the 21st Century emphasized that education must focus on mastering core academic subjects and developing 21st century skills. 2) Three significant competitive realities underline the need to dramatically redesign the curriculum: a) the two compulsory gaps faced by students due to exposure to VUCA - volatility, uncertainty, complexity, and ambiguity, b) fundamental changes in the economy, work, and business have reshaping workplaces and the nature of work that is driven by information, knowledge, innovation, and creativity, c) Fundamental changes in the economy, work, and business encourage the demands of different new skills more than ever before, individuals must be able to carry out non-routine creative tasks. 3) the design of the self-regulated learning phase using Accelerator's web-based learning system whose processes repeat and oppose linear development. 4) Due to the increasing rate of change in skills needed by career-oriented graduates, the review cycle tends to be shorter than the five-year cycle by paying more attention to the input of graduate users as external actors. 5) Together review the core general standards of the country and partnerships with stakeholders for 21st Century Skills emphasizing that education must focus on mastering core academic subjects and developing 21st century skills.